Brucella-Induced Impairment of Decidualization and Its Impact on Trophoblast Function and Inflammatory Profile - Zavattieri, Lucia (2025)
Brucella infection is associated with an increased risk of adverse obstetric outcomes in humans and animals. Decidualization, a process involving structural and functional changes in endometrial stromal cells, is essential for proper trophoblast implantation and placental development. Trophoblasts migration and their ability to invade the decidua and to undergo tubulogenesis, critical for proper implantation and placental development, are normally promoted by decidual cells. We evaluated whether Brucella infection of human endometrial stromal cells (T-HESC cell line) affects their ability to decidualize and to promote trophoblasts functions. Infection of T-HESC cells with either B. abortus, B. suis or B. melitensis resulted in deficient decidualization (as revealed by reduced prolactin levels) and an increased production of proinflammatory chemokines (CXCL8 and CCL2) as compared to uninfected cells subjected to decidualization stimuli. In addition, conditioned media (CM) from infected decidualized T-HESC induced an inflammatory response (CXCL8, CCL2 and IL-6) in human trophoblasts (Swan-71 cell line) but reduced their ability to produce progesterone. Trophoblasts preincubated with this CM also had reduced migration, invasion and tubulogenesis capacities, and this impairment was mediated, at least in part, by CXCL8 and CCL2. Moreover, infection of decidual stromal cells impaired the adhesion and spreading of blastocyst-like spheroids formed by Swan-71 cells. Brucella infection also affected the chemotactic capacity of decidual stromal cells for trophoblasts. Overall, these results suggest that Brucella infection of endometrial stromal cells impairs key processes required for successful implantation and placental development.